2017
DOI: 10.1016/j.ynstr.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between circadian rhythms and stress

Abstract: Life on earth has adapted to the day-night cycle by evolution of internal, so-called circadian clocks that adjust behavior and physiology to the recurring changes in environmental conditions. In mammals, a master pacemaker located in the suprachiasmatic nucleus (SCN) of the hypothalamus receives environmental light information and synchronizes peripheral tissues and central non-SCN clocks to geophysical time. Regulatory systems such as the hypothalamus-pituitary-adrenal (HPA) axis and the autonomic nervous sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 195 publications
(165 citation statements)
references
References 167 publications
(213 reference statements)
3
152
0
10
Order By: Relevance
“…Circadian rhythms in the dorsal horn have been shown to alter phosphorylation of JNK and expression of the chemokine CCL2 via PER1 (Morioka et al, ), which correlates with increased mechanical hypersensitivity. While circadian entrainment of the spinal dorsal horn remains understudied, its control of the autonomic nervous system is well established (Buijs, Escobar, & Swaab, ; Dickmeis & Foulkes, ; Kalsbeek et al, ; Koch, Leinweber, Drengberg, Blaum, & Oster, ; Nicolaides, Charmandari, Chrousos, & Kino, ); interestingly, the role of circadian rhythms in sensory neuron physiology remains largely unknown, with few studies examining the circadian control of peripheral sensory neuron activity/function.…”
Section: Circadian Control Of Nervous and Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Circadian rhythms in the dorsal horn have been shown to alter phosphorylation of JNK and expression of the chemokine CCL2 via PER1 (Morioka et al, ), which correlates with increased mechanical hypersensitivity. While circadian entrainment of the spinal dorsal horn remains understudied, its control of the autonomic nervous system is well established (Buijs, Escobar, & Swaab, ; Dickmeis & Foulkes, ; Kalsbeek et al, ; Koch, Leinweber, Drengberg, Blaum, & Oster, ; Nicolaides, Charmandari, Chrousos, & Kino, ); interestingly, the role of circadian rhythms in sensory neuron physiology remains largely unknown, with few studies examining the circadian control of peripheral sensory neuron activity/function.…”
Section: Circadian Control Of Nervous and Immune Cellsmentioning
confidence: 99%
“…A recent study by Xia and colleagues found that peak protein expression of the NMDA receptor subunit NR2B was at zeitgeber time 1 (ZT) 4 in the SCN and dorsal horn of the spinal cord (Xia et al, 2016). Circadian rhythms in the dorsal horn have (Buijs, Escobar, & Swaab, 2013;Dickmeis & Foulkes, 2011;Kalsbeek et al, 2011;Koch, Leinweber, Drengberg, Blaum, & Oster, 2017;Nicolaides, Charmandari, Chrousos, & Kino, 2014); interestingly, the role of circadian rhythms in sensory neuron physiology remains largely unknown, with few studies examining the circadian control of peripheral sensory neuron activity/ function.…”
Section: Central and Peripheral Neuronsmentioning
confidence: 99%
“…Animals have developed an elaborate response system that becomes activated when they are exposed to stress. It involves an immediate response (within seconds) via activation of the autonomous nervous system and a slightly slower response (within minutes) via HPA‐axis‐mediated release of glucocorticoids (GCs) from the adrenals (Figure ; reviewed in Koch et al, ). Both responses are activated after internal or external sensory systems signal a stressful event (e.g., a decrease in blood pressure or the encounter of a predator) and forward this information to the limbic forebrain or the brain stem (Ulrich‐Lai & Herman, ).…”
Section: Neurobiology Of Stress (Catecholamines Hpa Axis)mentioning
confidence: 99%
“…Besides core body temperature cycles, the adrenal glands are main players in coordinating the molecular oscillations of all body clocks (reviewed in Koch et al, ; Figure ). All peripheral clocks express GC nuclear receptors of type 1 (Balsalobre et al, ).…”
Section: The Mammalian Circadian Systemmentioning
confidence: 99%
See 1 more Smart Citation